A Simple Technique to Ascertain the Phase Relationships between the Various Atomic Orbitals in Each Pi-Molecular Orbital for the Linear Polyenes - Khan, Mohamad Niyaz (1990)
A simple technique is suggested for the construction of phase relationships of interacting 2p-atomic orbitals (2P-AO) in each molecular orbital for pi-electrons (Pi-MO) in the linear polyenes, CnHn+2 with n ranging from 2 to 25.